Semigroups of composition operators in analytic Morrey spaces. - Galanopoulos, Petros; Merchán-Álvarez, Noel; Siskakis, Aristomenis G. (Springer Nature, 2020)
Analytic Morrey spaces belong to the class of function spaces which, like BMOA, are defined in terms of the degree of oscillation on the boundary of functions analytic in the unit disc. We consider semigroups of composition operators on these spaces and focus on the question of strong continuity. It is shown that these semigroups behave like on BMOA.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/15630?template=romeo
Keywords: Operadores lineales; Morrey spaces; Morrey; BMOA; Semigroups of composition operators; Semigroups; Composition operators